Lipid biomarkers of GVHD in allogeneic stem hematopoietic cell transplantation patients - Lin, Zhi; Shen, Jie; Fu, Yicheng; Liu, Jiao; Yan, Lu; Li, Xin; Yang, Minghua (Frontiers in Immunology, 2025)
ObjectiveWhile dyslipidemia is established as a key modulator of innate and adaptive immune responses, its role in hematopoietic reconstitution remains unclear. This study aimed to characterize lipid profiles in patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT) and evaluate the associations between dyslipidemia and clinical outcomes.MethodsA retrospective analysis was conducted in a cohort of 106 adult patients (≥18 years) who underwent allogeneic HSCT between January 2019 and December 2023 and had complete lipid records.ResultsProfound dyslipidemia was observed post-transplantation, with over 60% of patients developing significantly decreased high-density lipoprotein cholesterol (HDL-C) and elevated triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) compared to baseline. HDL-C reached its nadir around day 14 and recovered slowly thereafter. Patients with grade III–IV acute graft-versus-host disease (GVHD) exhibited significantly lower HDL-C levels compared to those without GVHD. Lower HDL-C levels were correlated with delayed neutrophil engraftment and inferior GVHD-free/relapse-free survival (GRFS), though not with overall survival (OS). An HDL-C threshold of ≤0.84 mmol/L was identified as an independent predictor of GVHD.ConclusionEarly post-transplant HDL-C dynamics represent a promising biomarker for GVHD risk stratification. These findings support the incorporation of protocolized lipid monitoring into HSCT management to guide preemptive therapeutic interventions.